Green Hydrogen Co-Firing Policy: A Decarbonization Strategy for Coal-Fired Power Plants in Indonesia: Kebijakan Co-firing Hidrogen Hijau: Solusi Dekarbonisasi Pembangkit Listrik Tenaga Uap di Indonesia - Darmawan, Christhoper Kristian; Sebastian, Ezra (Universitas Islam Indonesia, 2025)
The purpose of this study is to analyze the urgency of implementing green hydrogen co-firing as a more sustainable alternative to biomass, both from the legal and implementation aspects, and to formulate the optimization steps needed to support the implementation of green hydrogen co-firing in order to achieve the NZE 2060. This study uses a normative-empirical method, with a legislative approach to review and evaluate the applicable regulatory framework and energy policies, linked to the empirical conditions of co-firing implementation in Indonesia. The results show that green hydrogen has significant potential as a blended fuel that is more environmentally friendly and sustainable than biomass. However, its implementation still faces various challenges, especially related to regulatory readiness, the availability of hydrogen infrastructure, the need for economic incentives, and investment support. This study also concludes that the implementation of green hydrogen co-firing is not only relevant to support the achievement of the NZE 2060, but also contributes to strengthening environmental sustainability and national energy security, as long as it is supported by comprehensive and integrated policies.